The attitudes and perceptions of secondary school pupils in Transkei towards geography: a case study of the Butterworth district - Sarpong, Emmanuel (Rhodes University, Faculty of Education, Department of Education, 1992)
Considerable attention has in recent times been given to the attitudes of secondary school pupils towards Geography among black schools in South Africa. Many reasons account for this. It is partly because of the poor results and falling numbers of pupils in the discipline. Concern has also been expressed on the relevance of the Geography syllabus to the black pupils. Evidence suggests that these problems are evident in Transkei. The need therefore exists to assess pupils' attitudes towards Geography in Transkei. Arising from this background, this study sets out to assess the attitudes of secondary school pupils in Transkei towards Geography. Two hundred and thirty four pupils from eight urban and rural secondary schools in the Butterworth District of the Republic of Transkei were used in the study. Attitudes were measured in terms of "interest in Geography", "desire to study the discipline", "commitment to Geography" and the perceived relevance of the discipline. Through the use of techniques such as percentages, chi-square and principal component analysis - among others - for the analysis of the data, the following information emerged from the study: (1) Geography is generally perceived as being worthy of study; (2) Differences in responses were noted to result from a complex of factors which were grouped into home environmental factors and school environmental ones. (3) The major factor influencing attitudes towards Geography was noted to be home environmental conditions.In general pupils from lower income families expressed more positive views about the worth of Geography than those from the upper income families. From the above findings, it has been proposed that teachers and educational planners need to be made aware of these findings as they are important for classroom practice. It has also been recommended that there is a need to improve certain school practices such as taking pupils on Geography excursions more often as factors such as this were shown to improve pupils' attitudes towards the discipline.
Keywords: Students, Black -- South Africa -- Attitudes; Geography -- South Africa -- Transkei -- Study and teaching (Secondary)